ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Febriany Utami; Etty Murwaningsari (Jurnal Magister Akuntansi Trisakti, 2017)
The purpose of this research is to know empirically influence of of profitability ratios with stock returns that are moderated by dividend policy to see the description of decisions investors will take. Return on the results (gain or loss) obtained from a stock investment This research sample is 43 companies listed on the Indonesia Stock Exchange from 2012-2015. Sampling technique is purposive sampling method. The method of analysis used is moderated regression analysis. The result of the research shows that ROA, ROE, DPR have a significant positive effect on Stock Return, while NPM and EPS have no significant effect on Return of Stock and Result of this research Dividend Payout Ratio (DPR) strengthens ROA, ROE, NPM to Return. While Dividend Payout Ratio does not strengthen Earnings Per Share (EPS) relationship to stock return.